Historical distribution of central nervous system tumors in the Mexican National Institute of Neurology and Neurosurgery - Lucinda Aguirre-Cruz; Edgar Rangel-López; Dora Luz de la Cruz-Aguilera; Citlali Ekaterina Rodríguez-Pérez; Luis Ruano; Leora Velásquez-Pérez; Mauricio Martínez-Moreno; Juan Garduño-Espinosa; Julio Sotelo (Instituto Nacional de Salud Pública, 2016)
Objective. To determine the frequency of central nervous system (CNS) tumors in the first fifty years of the National Institute of Neurology and Neurosurgery of Mexico Manuel Velasco Suárez (Instituto Nacional de Neurología y Neurocirugía de México, INNN) from 1965 to 2014. Materials and methods. A total of 16 116 institutional records of CNS tumors were analyzed. The frequency and distribution of CNS tumors were evaluated by tumor type, patient age and patient gender. The annual relationship between CNS tumors and surgical discharges (SD) over the last 20 years was estimated. Results. The frequencies of most CNS tumors were consistent with those found worldwide, and the most common tumors were neuroepithelial tumors (33%), particularly astrocytic tumors (67%); meningeal tumors (26%); and pituitary tumors (20%). The incidence of pituitary tumors in these data was twice as high as that reported in other regions of the world, and the relationship between CNS tumors and SD was consistent over time (0.22-0.39). Conclusion. This study summarizes the largest sample of CNS tumor cases analyzed in Mexico and provides an important reference of the frequency of this tumor type in the country. This work will serve as a basis for conducting studies evaluating factors associated with the presence of CNS tumors and for identifying adequate public health interventions.  DOI: http://dx.doi.org/10.21149/spm.v58i2.7786